Virtual Screening of Apigenin and Luteolin as Natural Aromatase Inhibitors for the Treatment of Breast Cancer Patients - Baydaa Hamad Obaid Saleh (Iraqi Journal of Industrial Research)
Aromatase is an enzyme that converts androgens (like testosterone) to estrogens (like 17- estradiol). It is also a highly successful therapeutic target for endocrine-responsive breast cancer. Aromatase inhibitors, which suppress estrogen synthesis in postmenopausal women, have been useful in the treatment of individuals with estrogen receptor-positive breast cancer. Anastrozole is an aromatase inhibitor medication that is used in the management and treatment of breast cancer. Flavonoids inhibit cancer cell proliferation by causing apoptosis, encouraging autophagy, and changing the cell cycle. Although several dietary flavonoids (like in parsley, celery and Broccoli) can inhibit aromatase, the tissue specificity and mechanism of binding are uncertain. According to several researches, flavonoids (apigenin and luteolin) dramatically suppress estrogen production. The study aims to examine binding of 3EQM (Aromatase) in the A chain with both of flavonoid (Apigenin and luteolin) and Anastrozole, using an in silico approach. PyRx default program was used to detect docking accuracy. Virtually, results showed that flavonoids have higher binding strength for apigenin and luteolin (which was -8.2 and -8.3) than Anastrozole (which was -7.6) with chain A of Aromatase. So, flavonoids can potentially be used as a natural medication to reduce breast cancer incidence. However, clinical trial studies are needed to investigate the role of apigenin and luteolin in the treatment of breast cancer.